Evaluating the Serum Levels of CCL17, CCL22, and CCL28 Chemokines and the Gene Expression of α4β1 and α4β7 Integrins in Patients With Allergic Rhinitis - Razieh Rezaeianpour; Ramin Lotfi; Seyed Hamidreza Mortazavi; Ali Gorgin Karaji; Alireza Rezaiemanesh; Farhad Salari (Acta Medica Iranica, 2024)
Allergic rhinitis (AR) is a chronic inflammatory disease involving the nasal mucosa. Leukocytes recruitment to the inflammation sites is controlled by chemokines, cytokines, and adhesion molecules. Retinoic acid (RA), a vitamin A metabolite, plays an essential role in mucosal immunity and the production of inflammatory cytokines and chemokines. This study intended to evaluate the serum levels of RA, CCL17, CCL22, CCL28, and the mRNA expression levels of α4, β1, and β7 integrins in AR patients compared to healthy subjects. Peripheral blood was collected from 37 patients with AR and 30 age- and gender-matched healthy individuals. Serum levels of RA, CCL17, CCL22, and CCL28 were measured by the enzyme-linked immunosorbent assay (ELISA) technique, and the mRNA expression levels for α4, β1, and β7 integrins were assessed using the quantitative real-time PCR method. Our results showed that the serum levels of CCL22 and CCL28 chemokines are significantly higher in the AR group compared to the healthy controls (P<0.01). However, the gene expression of the β1 integrin in the AR group was significantly lower than that of the control group (P<0.001). Besides, there was a positive association between serum RA and CCL17 levels in patients (P<0.0001, r=0.6). In conclusion, increased serum levels of CCL22 and CCL28 chemokines, as well as decreased gene expression of β1 integrin in AR patients, may contribute to the pathogenesis and/or exacerbation of AR.